Extended Producer Responsibility for waste televisions and computers: A regulatory evaluation of the Australian experience. (15th October 2017) - Lodhia, Sumit; Martin, Nigel; Rice, John
Abstract: High annual volumes of television and computer waste presents a challenge to Australian communities, resulting in the development of Extended Producer Responsibility (EPR) legislation. This study aims to establish, through the use of public interest theory, whether EPR legislation in Australia was in the public interest. Using a regulatory analysis, the results show that during the first 3 years of the scheme, over 130 liable parties joined co-regulatory arrangements each year to fund upstream recycling services for television and computer waste. In program terms, the scheme has been highly successful recycling over 130, 000 tonnes of metals, leaded and non-leaded glass, plastics and other materials while limiting landfill transfers to approximately 6900 tonnes, all at a cost of A$50–60 million per annum to producers. The scheme has also seen a range of upstream recycling partnerships established between the co-regulated administrators and formal technical and social enterprise waste management organizations. However, while the upstream material recovery rate is steady at approximately 95%, the results suggests that exporting waste for downstream processing will continue in the future. Analysis also points to substantial funding for 'over target' collections, downstream recycling infrastructure and landfill diversion strategies as critical for averting severe environmental impacts from e-Waste dumping. The study concludes by suggesting that while the successes of EPR scheme are in the public interest, its potential deficiencies could limit such benefits and therefore need to be addressed. Notably, the scheme could be enhanced through the application of improved recycling target methodologies, including the estimation and forecasting of domestic Waste Electrical and Electronic Equipment (WEEE) stock levels. Graphical abstract: Highlights: Australian communities generate over 460, 000 tonnes of e-Waste annually. Australia's EPR scheme recycled 130, 000 tonnes of e-Waste during 2012–2015. The EPR scheme costs to industry benchmarked at A$364–437 per tonne. Substantial volumes of e-Waste are exported for downstream processing. Low cost landfill dumping of e-Waste presents a major environmental challenge.